Identification of the Implementation Level of the Covid-19 Protocol in Service Providers Building (Case Study of Palu City Area) - Andi Asnudin; Anisa Dwi Syafira (International Association of Lowland Technology, 2022)
ABSTRACT Construction projects themselves are one of the aspects affected by Covid-19. Therefore, a rule is required to be used as a protocol in the implementation of work in the field of construction which in this case is the Instruction of the Minister of PUPR No.2 of 2020. This study aims to find out the level of Implementation of Covid Protocol in Construction Service Providers that located in Palu city . Technical research uses questionnaires based on samples from several contractors who are running projects in Palu City. Questionnaires that have been distributed are then analyzed using percentage and RRI methods. The results showed that the level of implementation of the Covid-19 protocol on construction projects based on sub indicators with the application rate is